Maternal risk factors for infant foster care from birth: A retrospective observational study - Inés Blanco Lara; Antje Horsch; Roger Hilfiker; Sarah Depallens; Vania Sandoz (Child Protection and Practice)
Background: Infant foster care may be necessary to avoid negative consequences for the infant linked to an abusive environment. Studies have found associations between such placement and negative outcomes for the child's development. This study investigated maternal perinatal risk factors associated with infant foster care at birth to improve the management of these situations. Objective: This retrospective observational study aimed to examine the associations between maternal perinatal risk factors and infant foster care at birth in a Swiss University Hospital. Participants and setting: The sample consisted of 386 mother-infant dyads. Eligibility criteria included referral to the Child Abuse and Neglect (CAN) Team from January 1, 2020 to December 31, 2022 and that the infant was alive at the hospital discharge. The local ethics committee approved the study. Methods: Based on the literature, the following maternal risk factors were selected: (1) personal history of abuse, (2) substance abuse, (3) psychiatric disorder, (4) minority of mother-to-be, (5) lack of post-compulsory education, and (6) psychological vulnerability. Chi-square tests of independence assessed the associations between the maternal risk factors and infant foster care. Results: Twenty-six (6.7%) newborns were placed at birth. Psychiatric disorder (p = 0.006), psychological vulnerability (p = 0.047), and alcohol and/or drug abuse (p=<0.001) were found to be significantly associated with child placement. Conclusion: Increased risks of infant foster care at birth were found when mothers had a psychiatric disorder, psychological vulnerability, or substance abuse. Implications for practice include developing healthcare structures tailored to this specific population, which may be associated with lower rates of mother-infant separation.